A quartz crystal microbalance method to quantify the size of hyaluronan and other glycosaminoglycans on surfaces - Srimasorn, Sumitra; Souter, Luke; Green, Dixy E; Djerbal, Lynda; Goodenough, Ashleigh; Duncan, James A; Roberts, Abigail R E; Zhang, Xiaoli; Débarre, Delphine; DeAngelis, Paul L; Kwok, Jessica C F; Richter, Ralf P (Scientific reports, 2022)
Hyaluronan (HA) is a major component of peri- and extra-cellular matrices and plays important roles in many biological processes such as cell adhesion, proliferation and migration. The abundance, size distribution and presentation of HA dictate its biological effects and are also useful indicators of pathologies and disease progression. Methods to assess the molecular mass of free-floating HA and other glycosaminoglycans (GAGs) are well established. In many biological and technological settings, however, GAGs are displayed on surfaces, and methods to obtain the size of surface-attached GAGs are lacking. Here, we present a method to size HA that is end-attached to surfaces. The method is based on the quartz crystal microbalance with dissipation monitoring (QCM-D) and exploits that the softness and thickness of films of grafted HA increase with HA size. These two quantities are sensitively reflected by the ratio of the dissipation shift (ΔD) and the negative frequency shift (- Δf) measured by QCM-D upon the formation of HA films. Using a series of size-defined HA preparations, ranging in size from ~ 2 kDa tetrasaccharides to ~ 1 MDa polysaccharides, we establish a monotonic yet non-linear standard curve of the ΔD/ - Δf ratio as a function of HA size, which reflects the distinct conformations adopted by grafted HA chains depending on their size and surface coverage. We demonstrate that the standard curve can be used to determine the mean size of HA, as well as other GAGs, such as chondroitin sulfate and heparan sulfate, of preparations of previously unknown size in the range from 1 to 500 kDa, with a resolution of better than 10%. For polydisperse samples, our analysis shows that the process of surface-grafting preferentially selects smaller GAG chains, and thus reduces the average size of GAGs that are immobilised on surfaces comparative to the original solution sample. Our results establish a quantitative method to size HA and other GAGs grafted on surfaces, and also highlight the importance of sizing GAGs directly on surfaces. The method should be useful for the development and quality control of GAG-based surface coatings in a wide range of research areas, from molecular interaction analysis to biomaterials coatings.
Keywords: Chondroitin Sulfates; Quartz Crystal Microbalance Techniques; mikrorovnovážné techniky křemenného krystalu; chondroitinsulfáty; buněčná adheze; kyselina hyaluronová; Cell Adhesion; Hyaluronic Acid; glykosaminoglykany; Glycosaminoglycans